Peran Haqiqah Dan Majaz Dalam Penafsiran Surah Al-Baqarah Ayat 2-5 Tentang Karakteristik Takwa - Naisyla Rahmadiah; Lela Nur Alifah (CV. ITTC INDONESIA, 2025)
The Qur’an is the holy book of Islam revealed in the Arabic language, which is clear and eloquent. To understand the Qur’an properly, one must have a good command of Arabic; without it, the Qur’an cannot be fully comprehended. The Qur’an, which contains teachings on monotheism (tawhid), law (shari‘ah), ethics (akhlaq), and many other aspects, employs various styles of expression to convey its meanings—one of which is majaz (figurative language). The use of majaz in interpreting the Qur’an involves different types, stages of emergence and development, as well as challenges and controversies that arise in Qur’anic interpretation. This study is a descriptive-analytical research. The conclusion of this research is that the majaz approach in Qur’anic interpretation is worth highlighting due to the numerous classifications of majaz and the intricate relationship between literal meaning (haqiqi) and figurative meaning (majazi). In Surah Al-Baqarah, verses 2–5, it is explained that the Qur’an serves as guidance for those who are pious (muttaqin). This article aims to examine the Qur’an as a source of guidance for the pious based on Tafsir al-Jalalayn of Surah Al-Baqarah, verses 2–5. The findings from Tafsir al-Jalalayn indicate that the Qur’an is the Book of Allah that provides guidance for those who are pious. However, contextually, this guidance does not come automatically from Allah SWT; it requires effort from individuals to seek and obtain His guidance. Furthermore, there are factors that can hinder one from receiving guidance (hudan), such as disbelief (kufr), for the hearts of disbelievers are closed to faith, preventing them from receiving guidance from Allah SWT.